Decreasing Blood Culture Contamination Rates Using A Specimen Diversion Device: A Quasi-Experimental Study. (October 2020) - Babiker, Ahmed; Ramakrishnan, Aditi; Howard-Anderson, Jessica; Holdsworh, Jill; Jacob, Mini; Jacob, Jesse
Abstract : Background: Blood culture contamination rates are frequently higher than the ≤3% standard in the emergency department (ED). Objective: We sought to determine whether the implementation of a blood diversion device that mechanically sequesters the initial aliquot of the blood culture sample decreased blood culture contamination rates. Methods: We performed a quasi-experimental study in two 500-bed hospitals. The blood-diversion device was implemented in the ED in hospital A, but not in hospital B, starting in January 2018. Preintervention data were collected over a 29-month baseline period, and postintervention data were collected for 20 months. Both hospitals provided ongoing feedback on contamination rates. Blood culture contamination was defined as presence of common skin microbiota (eg, coagulase-negative staphylococci) in only 1 of ≥2 blood culture sets collected within 24 hours. Preintervention and postintervention blood culture contamination rates were calculated based on total blood cultures collected and were compared within and between hospitals using the Wilcoxon rank-sum test. Changes in preintervention and postintervention total and ED contamination rates within hospitals were calculated as rate ratios (RRs) using interrupted time series (ITS) analysis with segmented Poisson regression. Results: Among 212, 789 total blood cultures (hospital A, 70, 005; hospital B, 142, 784), 4, 025 (1.8%) were contaminated. In hospital A, the intervention resulted in a decrease in overall median blood culture contamination rates (2.4% vs 1.4%; P < .001) and ED median blood culture contamination rates (4.7% vs 2.6%; P < .001), whereas in hospital B there was no significant change during the same period in overall (2.3% vs 2.0%) or ED (5.0% vs 5.0%) median blood culture contamination rates. In the ITS analysis, the intervention was associated with an immediate decrease in hospital A's contamination rate by 21.3% (level change RR, 0.79; 95% CI, 0.63–0.98; P = .04) overall and 21.0% (level change RR, 0.79; 95% CI, 0.62–1.0; P =.06) in the ED. After the intervention, there was a continued decrease in hospital A's overall (trend change RR, 0.95; 95% CI, 0.93–0.97; P < .001) and ED (trend RR, 0.94; 95% CI, 0.92–0.96; P < .001) blood culture contamination rates, but not in hospital B's overall (trend change RR, 1.02; 95% CI, 1.00–1.02; P = .01) or ED (RR, 1.00; 95% CI, 0.99–1.02; P = .30) blood culture contamination rates during the same period. Conclusions: Implementation of the blood diversion device in the ED resulted in a >20% relative reduction from a baseline of 5% of ED blood culture contamination rates. Continued improvement after implementation suggests ongoing efforts to address the workflow and the culture of safety are needed to optimize the use of this device. Funding: None Disclosures: None